Small vertebrates from Khasm El-Raqaba, late Middle Miocene, Eastern Desert, Egypt. (17th February 2016) - Gunnell, Gregg F.; Winkler, Alisa J.; Miller, Ellen R.; Head, Jason J.; El-Barkooky, Ahmed N.; Gawad, Mohamed Abdel; Sanders, William J.; Gingerich, Philip D.
Abstract : Khasm El-Raqaba (KER) (28.451°N, 31.834°E) is a large commercial limestone quarry in Egypt's Eastern Desert. The site is best known for cetacean fossils recovered from middle Eocene deposits, but remains of some geologically younger, small fossil vertebrates representing snakes, rodents and bats, have been recovered from karst fissure-fill deposits intrusive into the Eocene limestones. Comparisons with extant and extinct material reveal that the KER snakes represent two different colubrines, the rodents are referable to the ctenodactylid Africanomys, and the bats represent a new species of Hipposideros ( Pseudorhinolophus ). Together, faunal correlation and geological evidence are in broad agreement with a late Middle Miocene age for this KER fauna, and a palaeoenvironmental reconstruction of mixed subtropical and more arid microhabitats.